VOCATIONAL GUIDANCE TO FOSTER MOTIVATION TO WORK WITH BEGGARS, VAGRANTS, AND ABANDONED PEOPLE - Nihayah, Ulin; Novitasari, Retno Dwi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
The number of unemployed people continues to increase in Indonesia, causing an increase in cases of beggars, homeless people, and abandoned people. The inability to meet needs and lack of skills make begging and vagrancy an occupation. The government needs to intervene in this problem through social reintegration by providing vocational guidance. The aim is to encourage motivation to work and develop skills to prepare them for work after rehabilitation. The method used in this research is descriptive qualitative, to describe and illustrate the implementation of vocational guidance in fostering work motivation for PGOTs at the PGOT Mardi Utomo Social Service Home, Semarang. The results of the research show that the implementation of vocational guidance for PGOTs at the PGOT Mardi Utomo Semarang Social Service Home consists of an initial stage including the initial approach and assessment, a core stage namely the process of implementing vocational guidance, and the final stage includes resocialization and post-service. Vocational guidance material includes skills such as sewing, culinary arts, carpentry, animal husbandry, and making salted eggs. Instructors use individual and group methods, with guidance board media to facilitate understanding. After receiving vocational guidance at the PGOT Mardi Utomo Semarang Social Service Home, Beneficiaries experienced positive changes in that vocational guidance can grow their work motivation in terms of starting to develop their potential, showing an attitude of optimism in their career, and displaying an attitude of unity and ownership in their work.